Discussion note by Prof. Joop Evers: Profile of new intercity transport - Evers, Joseph J.M. (European Journal of Transport and Infrastructure Research, 2007)
The massive use of private cars causes serious problems. Despite parking problems and traffic congestions, for many the private car remains favourable. As an alternative, a new type of public intercity transport has been proposed, called Fast Transport on Request (FTR). Specific elements are: dedicated tracks for high speed bus driving between the cities; booking via Internet or intelligent telephone; intelligent logistics control reducing the number of stops and excluding detours; adaptive seats and digital facilities.